SME locator mobile application / Nur Azlina Khamis - Khamis, Nur Azlina (2015)
This project mainly focus in the development of SME Locator Mobile Application. This SME Locator Mobile Application is a mobile application that enables the users to view details and locate SMEs specializing in wholesale and retail trade services in Selangor which nearby to their current location. This application also supports navigation to the selected SME from current user location. With this application, SMEs owners are able to use it as a platform to promote their business and at the same time people who use it will be able to save cost and time in finding way to go to the SMEs. This project has three objectives that need to be achieve which are first, to identify requirements of the SME Locator mobile application, second is to design the SME Locator mobile application and third is to develop the SME Locator mobile application. Several methods have been applied for this project which are questionnaire with people to gather requirements for developing the application and also the review of related journals and articles for literature review to understand the process implemented in the project. This project uses Mobile Application Development Lifecycle (MADLC) for its development and it is developed for Android platform. Eclipse software was used for its development and it uses Java language and the database uses SQLite. The recommendations that is suggested for this project are the new added shop notifications to the users, the ability to share the shop's information through social media, the ability to make review regarding the shop and a feature which give the business owners their own page for them to make promotions and to show product that they are selling. Further details and explanation of SME Locator Mobile Application are described briefly in this report.